2017
DOI: 10.1111/ajag.12450
|View full text |Cite
|
Sign up to set email alerts
|

Talking to healthcare providers about sex in later life: Findings from a qualitative study with older Australian men and women

Abstract: Older people benefit when HCPs are proactive and ask about sexual health. Education in how to talk about sex with older people would also be beneficial for HCPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
(58 reference statements)
2
25
0
Order By: Relevance
“…Older people deserve sensitive, trained support to avoid concealing sexual problems and to ensure that deep-rooted cultural and gender issues are accepted and addressed (Yan et al 2011). Positive responses from healthcare providers can facilitate improved access to sexual healthcare (Fileborn, Lyons et al 2017). There is a need for more positive perceptions of older adults' sexuality in our culture, recognising the diversity of late-life sexualities and legitimising other avenues in which older adults can or may express their sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Older people deserve sensitive, trained support to avoid concealing sexual problems and to ensure that deep-rooted cultural and gender issues are accepted and addressed (Yan et al 2011). Positive responses from healthcare providers can facilitate improved access to sexual healthcare (Fileborn, Lyons et al 2017). There is a need for more positive perceptions of older adults' sexuality in our culture, recognising the diversity of late-life sexualities and legitimising other avenues in which older adults can or may express their sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…While discussion of sexual health is seen to be a core preventive health activity in general practice, especially for young adults, 5 qualitative research from Australia as well as the UK has suggested it is seldom raised between general practitioners (GPs) and older patients. 6,7 Yet older adults do have sexual health issues. A UK study of over 15,000 people aged 16-74 years showed the incidence of sexual difficulties increased with age, with more than 50% of sexually active people aged ≥60 years reporting at least one sexual difficulty in the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…16 Previous research has found that while some older adults are embarrassed to initiate sexual health discussions with GPs, 5 this patient group wants to be asked about and to have the opportunity to discuss their sexual health needs and concerns. 6 However, the sexual health of older patients is commonly unaddressed in policy documents and clinical guidelines. 17 It is likely that sexual health consultations within general practice would be welcomed by older patients, given this is the setting where most of their other healthcare needs are met.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers that older patients experience in discussing sexual health in medical contexts are of growing scientific interest. Older adults frequently report that being embarrassed or ashamed when initiating a conversation with a doctor about a sexual topic is a barrier to seeking help (Corona et al 2013 ; Fileborn et al 2017 ). Experiencing these feelings in this context is commonly associated with older individuals conforming to pervasive stereotypes about “asexual old age”.…”
Section: Introductionmentioning
confidence: 99%
“…Experiencing these feelings in this context is commonly associated with older individuals conforming to pervasive stereotypes about “asexual old age”. Also, the tendency of older adults to minimise the seriousness of sexual problems often leads them to feel anxious about their doctor’s reaction if a sexual issue is raised during a consultation (Gott and Hinchliff 2003 ; Moreira et al 2008 ; Bauer et al 2016 ; Fileborn et al 2017 ). The anticipated attitude of the health practitioner towards sex-related topics, together with their demographic characteristics (doctor’s gender, age, etc.…”
Section: Introductionmentioning
confidence: 99%